2017
DOI: 10.1016/j.ijpharm.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Epothilone B-based 3-in-1 polymeric micelle for anticancer drug therapy

Abstract: Epothilones are microtubule inhibitors that are promising alternatives to paclitaxel due to enhanced anticancer efficacy. While epothilones are slightly more water soluble than paclitaxel and more active against paclitaxel-resistant cells, they still require formulation with Cremophor EL and/or cosolvents and drug resistance still limits therapeutic efficacy. In this report, we showed that the combinational treatment of epothilone B (EpoB), 17-N-allylamino-17-demethoxygeldanamycin (17-AAG, Hsp90 inhibitor), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Ixabepilone, a semi-synthetic analog of epothilone B, belongs to synthetic chemo drugs with antimitotic properties for treatment of metastatic BC. Epothilones are defined as microtubule inhibitors, highly-effected against PTX-resistant cells [52]. Interestingly, higher effectiveness of Ixabepilone than PTX against resistant cells is caused by the different binding sites of the drug at microtubules.…”
Section: Chemotherapy For Breast Cancermentioning
confidence: 99%
“…Ixabepilone, a semi-synthetic analog of epothilone B, belongs to synthetic chemo drugs with antimitotic properties for treatment of metastatic BC. Epothilones are defined as microtubule inhibitors, highly-effected against PTX-resistant cells [52]. Interestingly, higher effectiveness of Ixabepilone than PTX against resistant cells is caused by the different binding sites of the drug at microtubules.…”
Section: Chemotherapy For Breast Cancermentioning
confidence: 99%
“…These drug solubilizers have their own adverse effects including peripheral neurotoxicity and hypersensitivity, and can disturb gastrointestinal function. In addition 17‐AAG delivered via DMSO or Cremophor EL has a short half‐life, limited ability to reach target cells, induction of drug resistance, poor specificity, and high hepatotoxicity that restrict its clinical use (Shin & Kwon, ).…”
Section: ‐Aag‐loaded Nanocarriersmentioning
confidence: 99%
“…In other research designed to enhance the water solubility of epothilone B, rapamycin, and 17‐AAG, Shin and Kwon loaded all three drugs into PEG‐b‐PLA micelles and reported high efficiency of these micelles against A549 cancer cells in vitro and in vivo (Shin & Kwon, ).…”
Section: ‐Aag‐loaded Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…As FEN has low water solubility, only small amounts of it would be present in the water. Hence, FEN would be well encapsulated in polymeric micelles [ 38 , 39 ]. DLS analysis revealed that the average particle size of the FEN-loaded Soluplus ® micelles was 68.3 nm.…”
Section: Resultsmentioning
confidence: 99%